Framing of charity TV advertisements in Egypt: A content analysis - Sherra, Maha (AUC Knowledge Fountain, 2017)
This study analyzed how charity organizations in Egypt utilize the use of framing, appeals, and strategies in their TV advertisements. A content analysis was conducted to understand the utilization of message framing; image valence/vividness; temporal framing; donations reframing; victim message strategy; source types; appeal types and execution framework; to enhance our understanding of the charity organizations' advertisement landscape in Egypt. The results indicate that framing is not a commonly used strategy by charity advertisers in Egypt, and the prevalent type of message framing in charity advertisements' is the gain frame, the most used temporal framing strategy is the long temporal framing, and the most used donation reframing strategy is the daily donation reframing. The results also indicate that the use of a negative image/story in their communication is very minimal compared to the prevalent use of a positive image/story. Regarding the victim message strategy, most of the advertisements included an unidentified group of three or more victims, and the most depicted victims are sick/ill children. The typical persons type of spokespersons is the most prevalent type followed by the use of celebrities. Finally, the altruistic appeal is most commonly used advertisement appeal, and the findings showed that charity advertisers rely on positive appeal characteristics and emotional appeal types rather than negative appeal characteristics and rational appeal types. This study also analyzed the congruency between message framing, image/story vividness, and advertisement appeal characteristics. The results revealed minimal congruency between message framing and image/story vividness, although showed congruency between the gain framed message and the positive appeal characteristic, while no congruency between the loss framed message and the negative appeal characteristic. The results also showed congruency between the positive and negative image/story vividness and the advertisement appeal characteristic, but minimal congruency between the neutral image/story vividness and the advertisement appeal characteristic. Finally, this study analyzed the spokespersons' gender, age group, and religion to identify the target groups of these advertisements, and to identify the used appeals to reach different target groups. The results showed that adult males are the most depicted in charity advertisements. Moreover, religious identification was not very common in charity advertisements which shows that charity advertisements target both Muslim and Christian groups, although during the coding process it was obvious that religious identification was associated with the nature of the advertised program or service. The results also showed that males were more depicted in advertisements with altruistic appeal, and adults were more depicted in guilt appeal and motivational appeal advertisements.